Cuckoo Search Algorithm for Optimize Reliability of Reduction Oxygen Supply System - Hamza Abd Alsharify, Fouad (Pure Sciences International Journal of Kerbala, 2024)
The goal of this paper is to maximize reliability of the spacecraft's oxygen reduction system at the lowest possible cost. The cuckoo algorithm was used with cost constraints based on two cost functions (sine and cosine). There was a comparison between the results of these two cost functions, where the best reliability of the system was obtained using the cosine function, and at a slightly higher cost when using the sine function. The goal of this paper is to maximize reliability of the spacecraft's oxygen reduction system at the lowest possible cost. The cuckoo algorithm was used with cost constraints based on two cost functions (sine and cosine). There was a comparison between the results of these two cost functions, where the best reliability of the system was obtained using the cosine function, and at a slightly higher cost when using the sine function.